Collaborative service delivery to address public health issues within a musculoskeletal setting: evaluation of the Healthy Mind, Healthy Body project. (2nd November 2019) - Holehouse, Kelly; Oliver, Karen; Rawlinson, Gillian; Roddam, Hazel
Abstract : Background/Aims: There is a need for greater focus on public health and its impact on musculoskeletal conditions within healthcare delivery. Physiotherapists are well positioned to support this. Outpatient physiotherapy musculoskeletal services traditionally focus on rehabilitation and physical exercise, yet many service users require support to improve both their mental and physical health. This innovative service improvement aimed to embed integrated health promotion within musculoskeletal physiotherapy service delivery. Methods: A physiotherapy-led multidisciplinary team introduced patients to other community-based support services to address wider health needs. Results: Service evaluation demonstrated a high uptake of self-referral to community services, validating the potential benefit for musculoskeletal condition management. Positive patient feedback indicates that patients valued the service and were well-supported to engage with health improvement. Conclusions: Musculoskeletal physiotherapy services need to consider the wider aspects of health, putting public health at the heart of musculoskeletal service delivery.